Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Step-by-step explanation:
7x(x - 2y)
= 7x.(x - 2y)
= 7x² - 14xy
= (2 + 1)(+5)
= (3)(5)
= 3 × 5
= 15
Step-by-step explanation:
1) 7x(x - 2y)
= (7x . x) - (7x . 2y)
= 7x² - 14xy
2) (2 + 1)(+5)
= 3(+5)
= (3 . +5)
= (3 . 5)
= 15
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.